CHINA’S INTRUSION IN AFRICA: DEVELOPMENT OR SEARCH FOR MARKET - Jenyo, Olajumoke Ganiyat; Kolawole, Afolabi Kamaldeen (IJRDO - Journal of Business Management, 2017)
The intrusion of China in Africa seems to be one of the African contemporary stories, but evenscholars and analyst found it hard to decide whether this cordial and growing relationship will behealthy for Africa in the long run. This paper examines the impacts of China’s intrusion in Africawhether it has yielded development or just for market searching. Sino- African Economic and Technical Cooperation were guided by four principles, namely equality, bilateralism, effectiveness and co-development. According to dependency theory, it indicates that Africa isengaging China because China wants to engage with Africa. Whatever interest China might beharbouring in engaging herself with Africa, their actions will be defined by African governments and organizations they are dealing with. This principle is more of a notice of China’s supportframework, which provides a favourable condition for the countries in Africa and most importantly the “no political strings” issue coupled with the Beijing’s willingness to provide aid and concessional loans. The principle will serve as development to some Africa countries andalso bring forth “Beijing Consensus,” with its strong obligation to Africa. In return, it helps inboosting the market of both African and China with the import and export markets between them, making the relationship to yield so many benefits. The relationship can be best describedas a symbiotic relationship as both parties have where the relationship benefits them. It can be identified as a way of development to Africa and market search for the China as well. A Hugebenefit to be derived by two parties from the relationship is encouraged. It is desirable because it eliminates behavioural outcomes for Africa leaders